Alkali-Activated Metashale Mortar with Waste Cementitious Aggregate: Material Characterization - Petr Hotěk; Lukáš Fiala; Wei-Ting Lin; Yi-Hua Chang; Robert Černý (Materials Proceedings, 2023)
The design of sustainable construction materials is continuously gaining increasing importance in civil engineering. Geopolymers are attractive alternatives to cementitious materials in terms of environmental impact and specific material properties, such as durability, an initial increase in mechanical properties, or chemical and thermal resistance. Such favorable properties can be advantageously utilized within various applications involving the design of materials for heavily stressed industrial floors. The research presented in the paper was focused on the design of a geopolymer composite based on metashale MEFISTO L05 and waste metashale RON D460HR binders. The 1:4 raw/waste mix of binders activated by potassium hydroxide/silicate was supplemented by 0.11 wt.% of graphite fibers to optimize electrical properties and bestow on it some new material functions, such as self-heating. The further utilization of fine waste aggregate (crushed defective concrete products, waste concrete from auto-mixers) resulted in an ~85% utilization of input waste materials. An acceptable mechanical performance of the mortar for particular civil engineering applications was observed (28d: Rf ~ 2.5 MPa, Rc ~ 15 MPa), as well as favorable thermal and DC/AC electrical properties, predicting the self-heating potential.